Seed germination and seedling growth of ramin (Gonystylus bancanus Miq.) on various growing media - NING WIKAN UTAMI; WITJAKSONO WITJAKSONO; DJADJA SITI HAZAR HOESEN (Biodiversitas Journal of Biological Diversity, 2006)
A study on seed germination and seedling growth of ramin (Gonystylus bancanus Miq.) was conducted at a green house, Treub Laboratory, Botany Department, Research Center for Biology- LIPI, Bogor. This study was to know the effect of growth media on the germination and growth of ramin. A Completely Randomized Designed with 13 treatments and 4 replications was used in this study. Thirteen compositions of growth media used were soil, compost, cocopeat, mixture of soil and compost (1:1; 1:3), soil, compost and cocopeat (1:1:1); soil, compost, cocopeat and goat manure (1:1:1:1); soil and cocopeat (1:1; 1:2; 1:3); compost and cocopeat (1:1; 1:2; 1:3); compost and husk of rice. The result showed that the highest germination percentage was 95% obtained on the cocopeat media, while on control (soil) was 55%. The highest germination value was 6.67 obtained from the mixture media of soil+compost = 1:3 and the lowest was 1.87 from the control. There was variation of leaf shape observed until 60 days after planting. Some compositions of suggested media for seed germination andseedling growth of ramin were cocopeat, mixture of compost+cocopeat (1:1; 1:2 and 1:3), compost and the mixture of soi+compost (1:2 and 1:3) respectively. Generally, germination and growth of ramin seem not to be restricted on growth media with special pH.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: germination, growth, ramin, Gonystylus bancanus Miq.